Selective Immunoglobulins deficiency in relatives antibody deficiency patient - Yralys Naranjo Herrera; María del Carmen Chávez Alfonso; Valia Concepción Ulloa; Cándido Marcos León Márquez; Grace Alicia De Lara García; Ernesto Gabriel Caraballosa Yero (Acta Médica del Centro)
Introduction: one of the most common inborn errors of immunity is selective IgA deficiency. Objetive: determine the prevalence of selective IgA deficiency   in first-degree relatives of patients diagnosed with this immunological deficiency included in the registry of inborn errors of immunity in Sancti Spiritus province until 2023 year. Methods: a cross-sectional descriptive study was carried out in Sancti Spiritus province from July 1st,2020 to December 31st, 2023.The population was made up of 36 first-degree relatives of the 15 patients with selective IgA deficiency diagnosed, included in the Provincial Registry of inborn errors of immunity. The three relatives with serum IgA dosage below normal values for their range of age were respondents. Results: decreased IgA and IgG values were found only in some first-degree relatives and all showed IgM and CD3+CD4+T lymphocyte numbers within normal parameters. Female patients, adults and the mother as a predominated relative, most of them being asymptomatic. Conclusions: In a fifth part of the families with selective IgA deficiency patient studied, new cases with this immunological deficiency appeared. Asymptomatic disease was the most frequent phenotype.